Development of Hot Wire-Laser Beam Displacement Technique for Determining Thermal Conductivity and Thermal Diffusivity of Nanofluids - Mohammed Ali, Faris (2011)
A nanofluid is a fluid containing suspended nanoparticles, with sizes of the order of nanometer. Heat conductors of nanofluid are better than that of base fluid. Therefore, the most important point to know is its thermal conductivity and thermal diffusivity. The focus of this work is on determining the thermal conductivity and thermal diffusivity of nanofluids containing metallic and non metallic nanoparticles. The specific objectives were the determination of the effects of sonication time, volume fraction concentration, particle size, particles materials, and two materials mixture nanoparticles on the thermal conductivity and thermal diffusivity of nanofluids. Thermal conductivity and thermal diffusivity measurements were performed by hot wire-laser beam displacement technique. The hot wire-laser probe beam displacement setup consists of a CW He-Ne laser beam as the probe beam, a thin circular Ni-Cr alloy resistance wire which serves as a heat source, and a position sensitive detector (PSD). The developed coupled transient heat conduction equations of the heating wire and the nanofluid were solved simultaneously by using the Finite Difference Method. A numerical model, which took the thermal conductivity and thermal diffusivity of the test nanofluids as parameters to calculate the probe beam deflection, was established separately. By comparing the time-varying deflection curve from the numerical model with that recorded in the experiment, the nanofluids thermal conductivity and thermal diffusivity in the model were adjusted to give the best agreement between the model and the experimental results. The nanofluid samples were aluminum (Al) 18 nm, chromium (Cr) 20 nm, and aluminum oxide nanoparticles (Al2O3) 11 nm, 25 nm, 50 nm, and 63 nm dispersed in distilled water, ethylene glycol,and ethanol. These nanofluid samples were prepared using the one-step method. The results of the thermal conductivity and thermal diffusivity measurements showed the best interval time of sonicated was 6 hours. The results showed that the thermal conductivity and thermal diffusivity of all samples of nanofluid increased linearly with increases of volume fraction concentration of nanoparticles in base fluid. Where, the thermal conductivity of Al nanofluid suspension in distilled water at volume fraction concentration between 0.42 % to 0.085 was 0.732 W/m.K to 0.648 W/m.K,respectively. The results of the thermal conductivity and thermal diffusivity measurements of Al2O3 nanofluids containing different sizes of nanoparticles (11 nm to 63 nm) showed that the smaller nanoparticles yielded lower thermal conductivity and thermal diffusivity. Where the thermal conductivity of Al2O3 of particles size 11 nm suspension in distilled water at volume fraction concentration 1.4 % was (0.676 W/m.K) and thermal diffusivity was (1.727x10-7 m2/s), while the thermal conductivity and thermal diffusivity of Al2O3 of particle size 63 nm at the same volume fraction concentration was 0.705 W/m.K and 1.793x10-7 m2/s, respectivilly. This means that the thermal conductivity and thermal diffusivity have increased with increase particle size. The result also showed that the thermal conductivity and thermal diffusivity depended on the material of the nanoparticles, where the thermal conductivity and thermal diffusivity of metallic nanoparticles higher than the nonmetallic nanoparticles. Measurement of thermal conductivity and thermal diffusivity of bimetallic nanofluid was also conducted, and the result showed that the thermophysical properties of two metallic mixture nanofluids improved 15.82 % - 7.94 % for bimetallic in water, 17.44 % - 9.3 % in ethylene glycol, and 19.65 % - 10.4% in ethanol.